A model and experimental investigation of belt noise in automotive accessory belt drive system. (12th May 2004) - Sheng, Gang; Liu, Keming; Otremba, Jerzy; Pang, Jian; Qatu, Mohamad; Dukkipati, Rao
This paper presents a model to characterise V-ribbed belt (Micro-VTM) noise in accessory belt drive system (ABDS), or front-end accessory drive (FEAD) of automotive engines. It has been known that radial friction-induced vibrations generate belt misalignment noise and tangential friction-induced vibrations relates to belt slip noise. In this study, these two kinds of vibrations are found essentially different, and they are formulated mathematically by using forced vibration equation and self-excited vibration equation respectively. The formulations are consistent with conventional experimental results. A series of new tests were run to assess the properties of the belt noise using industry standard test rigs. The test results are agreeable with the results derived directly from the formulations. The proposed model is expected to provide accessory drive designers with insight into the issues associated with improving the overall noise performance of ABDS system.